2022
DOI: 10.1001/jamanetworkopen.2022.40399
|View full text |Cite
|
Sign up to set email alerts
|

Death and End-of-Life Care in Emergency Departments in the US

Abstract: ImportanceThere are more than 140 million annual visits to emergency departments (EDs) in the US. The role of EDs in providing care at or near the end of life is not well characterized.ObjectiveTo determine the frequency of death in the ED or within 1 month of an ED visit in an all-age, all-payer national database.Design, Setting, and ParticipantsThe retrospective cohort study used patient-level data from the nationally representative Optum clinical electronic health record data set for 2010 to 2020. Data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
3
10
1
Order By: Relevance
“…We find that ED mortality at the onset of the first pandemic wave at least doubled in non-COVID older patients and tripled in COVID older patients compared to pre-pandemic older patients seen in the same EDs. This mortality is higher than that found in other studies prior to the pandemic [4,5].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…We find that ED mortality at the onset of the first pandemic wave at least doubled in non-COVID older patients and tripled in COVID older patients compared to pre-pandemic older patients seen in the same EDs. This mortality is higher than that found in other studies prior to the pandemic [4,5].…”
Section: Discussioncontrasting
confidence: 66%
“…Among these outcomes, death accounted while patient is being attended in the ED (ED mortality) is one of them, and it is one of ED quality marker most frequently used. The ED mortality affected 0.20-0.30% of overall patients and was most common among patients who are older and with chronic comorbidities [4,5]. In many cases, they are older patients with trauma or at the end of life.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report of the association of CA incidence and outcomes at a neighboring hospital system adjacent to a ransomware-infected HDO. The increase in CAs mirrored the increase in strokes previously reported during the same time period (5). Additionally, we analyzed the 4-year period before the ransomware cyberattack using an ARIMA model to account for seasonal and secular variation.…”
Section: Discussionsupporting
confidence: 52%
“…This hypothesis is consistent with prior studies that found events resulting in increased EMS diversions, such as marathons, are associated with longer ambulance transport times and higher 30-day mortality (10). Although increased EMS diversion time has been previously reported related to this event (5), we do not have complete data regarding EMS transport times to determine if diversions were relevant to our specific CA cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation